Temperature Affects Voltage-Sensitive Conductances Differentially in Octopus Cells of the Mammalian Cochlear Nucleus - Cao, Xiao-Jie; Oertel, Donata (Journal of neurophysiology, 2005)
Department of Physiology, University of Wisconsin, Madison, Wisconsin Submitted 6 October 2004; accepted in final form 30 March 2005 Temperature is an important physiological variable the influence of which on macroscopic electrophysiological measurements in slices is not well documented. We show that each of three voltage-sensitive conductances of octopus cells of the mammalian ventral cochlear nucleus (VCN) is affected differently by changes in temperature. As expected, the kinetics of the currents were faster at higher than at lower temperature. Where they could be measured, time constants of activation, deactivation, and inactivation had Q 10 values between 1.8 and 4.6. The magnitude of the peak conductances was differentially affected by temperature. While the peak magnitude of the high-voltage-activated K + conductance, g KH , was unaffected by changes in temperature, the peak of the low-voltage-activated K + conductance, g KL , was reduced by half when the temperature was lowered from 33 to 23°C ( Q 10 = 2). Changing the temperature changed the kinetics and the magnitude of the hyperpolarization-activated mixed cation conductance, g h , but the changes in magnitude were transient. The voltage sensitivity of the three conductances was unaffected by temperature. The action of temperature on these conductances is reflected in the resting potentials and in the shapes of action potentials. Address for reprint requests and other correspondence: D. Oertel, Dept. of Physiology, University of Wisconsin Medical School, 1300 University Ave., Madison, WI 53706 (E-mail: oertelatphysiology.wisc.edu )